Detection of water, oil and oil contamination in water using chirped fiber Bragg gratings inscribed in CYTOP fibers - Leal, Arnaldo G.; Campos, Vinícius; Theodosiou, Antreas; Frizera, Anselmo; Kalli, Kyriacos; Marques, Carlos Alberto F. (My University, 2020)
Water and oil detection as well as oil (or water) in water (or oil) estimation play important roles in the oil processing industry due to advantages such as reduction of the residence time of oil in oil-water separation units (or three-phase oil separators), increasing of the oil purity and avoiding environmental issues regarding the disposal of water contaminated with oil. In addition, it also enables the detection of water contamination in fuels with important impacts on the environment and oil quality. Advantages such as lightweight, multiplexing capabilities, water affinity and electromagnetic fields immunity make polymer optical fibers (POFs) an interesting option for detecting water and oil contamination. This paper presents the development of a POF sensor for oil, water and oil in water detection using chirped fiber Bragg gratings (CFBGs). The grating structure was inscribed in cyclic transparent optical polymer (CYTOP) fibers through the plane-by-plane method using a femtosecond laser. The CFBG is submerged in the liquids (water, mineral oil and their mixture) in order to verify the ability of such sensor of performing temperature independent measurements, which is accomplished by analyzing not only the central reflected wavelength, but also the full width half-maximum. The results indicate the capability of the proposed sensing approach of detecting oil and water. Furthermore, oil contamination as low as 0.1% (in volume) in water was detected using the CFBGs inscribed in CYTOP fibers. Therefore, the results depicted in this work can result in reliable systems for oil or water quality monitoring, which finds important application in oilfields and process industry.
Keywords: Chirped fiber Bragg gratings; CYTOP fibers; Oil and water detection; Optical fiber sensors; Polymer optical fibers